SYNTHESIS CHARACTERIZATION AND ANTIBACTERIAL ACTIVITY OF IRON OXIDE NANOPARTICLES AGAINST STAPHYLOCOCCUS EPIDERMIDIS - SANGWAN, POONAM; KUMAR, HARISH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study deals with the synthesis of iron oxide nanoparticles by sol-gel technique, their characterization and antibacterial activity of these nanoparticles against Staphylococcus epidermidis. Methods: Hematite (α-Fe2O3) nanoparticles were successfully synthesized by sol-gel method using tetraethyl orthosilicate as a precursor. The structural morphology, size, and chemical state of synthesized iron oxide nanoparticles have been investigated by X-ray diffractometer (XRD), transmission electron microscopy, Fourier transform infrared spectroscopy, and ultraviolet-visible spectroscopy. The antibacterial activities of these iron oxide nanoparticles were investigated on a pathogenic bacteria S. epidermidis, by measuring the zone of inhibition and colony-forming units on solid medium and by measuring the optical density of the culture solution. Antibacterial activity of iron oxide nanoparticles was also compared with well-known standard antibiotics. Results: It was confirmed from XRD data that the synthesized iron oxide nanoparticles were hematite (α-Fe2O3) nanoparticles. Average particle size of the Fe2O3 nanoparticles was found to be 38.57 nm by XRD characterization. The antibacterial activity of Fe2O3 nanoparticles was almost comparable to the most of the standard antibiotics (taken for comparison), but Fe2O3 nanoparticles were found to be more effective than antibiotic ampicillin and sulfatriad toward S. epidermidis. Conclusion: This study shows that Fe2O3 nanoparticles possess good antibacterial properties; therefore, these metal nanoparticles may be used in place of antibiotics. These inorganic metal nanoparticles can be used by pharmaceutical industries for further research regarding the toxicity study for its use in human being.